Case Report: Long-term metabolic response of metastatic uveal melanoma to pembrolizumab on FDG-PET/CT despite a serial pseudoprogressions phenomenon - Amrane, Karim; Le Meur, Coline; Thuillier, Philippe; Dzuko Kamga, Jacques; Alemany, Pierre; Chauvelot, Frederic; Niel, Clémence; Bellange, Alex; Abgral, Ronan (Frontiers in Immunology, 2023)
Uveal melanoma (UV) is a rare and aggressive melanoma with poor 1-year survival. up to 50% of UV patients develop metastases, mainly to the liver.Here, the authors present a 2-deoxy-2-[ 18 F] fluoro-D-glucose positron emission tomography ( 18 F-FDG-PET) study of a very rare case of secondarily metastatic UV in an 81-year-old Caucasian with a dramatic response to pembrolizumab associated with serial pseudogression.18 F-FDG-PET associated with clinical status and peripheral blood derived neutrophil-tolymphocyte ratio (dNLR) were performed to guide therapeutic strategy due to an atypical pseudoprogression phenomenon.